Management of creative and cultural enterprises: a study of an organization of education and dissemination of Afro-Brazilian rhythms in São João del Rei (MG) - Judice, Valéria Maria Martins; Furtado, Sandra Cristina (Organizações & Sociedade, 2014)
Creative industries are characterized by production of artistic and symbolic goods involving interpretative, aesthetic, experiential consumption. This differentiates them from conventional industries, with products/services geared to functional and/or instrumental consumption and usually the main focus of Administration studies. This paper is aimed at describing and analyzing a creative and cultural enterprise in São João del-Rei (MG/Brazil), in order to understand organization, management, products, objectives, and as reported in the literature, the existence of specific tensions. The methodology of case study was adopted, with an interpretative approach, involving data collection and analysis carried out via: (a) in-depth interviews with members and partners of the association; ( b) non-participant observation of public organizational events performed by the organization and (c) information retrieved from the organization’s website. Found results evidenced in the studied organization the existence of typical dilemmas of literature, particularly the “art vs. business” tension, with partial acceptance of management, improvisation tendency, absence of long range planning and emphasis on/ or idealization of educational objectives.